Pengaruh Penanaman Materi Shalat Pada Pembelajaran PAI Terhadap Pelaksanaan Shalat Fardhu Peserta Didik Kelas VII di SMPN 1 Bukittinggi - Saputra, Andi; A, Alimir (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study was motivated by the discovery that several students of Class VII of SMPN 1 Bukittinggi did not pray even though the teacher had made every effort to pass on prayer materials. Often delays prayer time. Prioritize other work instead of praying five times a day. By teaching students prayer materials, there is great hope that this will improve students' implementation of fardhu prayer. Thus, this study aims to determine the effect of embedding prayer materials into PAI learning on students' implementation of fardhu prayers. The research used in this study is quantitative correlational research. The population in this study consisted of all students from class VII of SMPN 1 Bukittinggi, a total of 202 students. The sample in the study included 15% of the population using random sampling techniques and obtained 31 students as samples. Data were collected through a questionnaire and analyzed using a simple linear regression test. Based on the results of research conducted, it was found that planting prayer materials had an effect on the implementation of fardhu prayers for class VII students at SMPN 1 Bukittinggi, as shown by the sig value in the simple linear regression test. of 0.000 < 0.05 and the calculated t-value > t-table, which was 3.431 > 2.045 and the influence was 28.9% and the rest was influenced by other factors not explored in this study.